The Effect of Auditory Stimulation Spiritual Emotional Freedom – Technique Care (ASSEF- TC) Towards Elderly Anxiety in Werdha Nursing Home Surabaya - Has, Eka Mishbahatul M; Pradany, Risna Nur; Wahyuni, Sylvia Dwi (International Journal of Psychosocial Rehabilitation, 2020)
The problem that often occurs in the elderly is anxiety, and if it happens continuously, depression, other emotional illnesses, and even physical illness may occur. Decreasing the degree of stress can be done with several techniques, including Auditory Stimulation Care (ASC) and Spiritual Emotional Freedom Technique (SEFT). The researcher combines these two techniques, which expected to provide a more optimal effect. This study aims to analyze the impact of ASSEF-TC on elderly anxiety in Werdha Nursing home Surabaya. This research uses to experiment with one group of pre-post designs. The number of the population was 36, and the sample was 17 respondents using purposive sampling. The independent variable is the ASSEF-TC, and the dependent variable is the anxiety level. The data collection instruments used the questionnaire of the Geriatric Anxiety Inventory (GAI) and were analyzed with the Wilcoxon sign rank test (α=0.05). The results showed the scale of respondents’ anxiety after being given ASSEF-TC technique for 15 consecutive days decreased. The analysis test using the Wilcoxon sign rank test indicates that there is an effect of the ASSEF-TC technique on elderly anxiety (p=0.000). This study found that there is a significant effect of the ASSEF-TC technique on reducing stress in the elderly. From the result of the study, it is hoped that the board management can implement the ASSEF-TC method to reduce the degree of anxiety of the elderly regularly.